Water-uptake in hollow glass microspheres and their influence on cathodic and anodic delamination along the polymer/metal-interface. (March 2022) - Singewald, Tanja Denise; Bruckner, Thomas Maximillian; Gruber, Ralph; Schimo-Aichhorn, Gabriela; Hader-Kregl, Laura; Poeller, Sascha; Mueller, Mathias; Kern, Carina; Luckeneder, Gerald; Stellnberger, Karl-Heinz; Strauß, Bernhard; Hafner, Martina; et al.
Abstract: Water-uptake in hollow glass microspheres (HGM) filled polymers, and in turn corrosion processes along the polymer/metal-interface are not well studied to date. Here, we examine water absorption and diffusion of two epoxy adhesives in the absence and presence of HGM on zinc coated steel using electrochemical impedance spectroscopy and height-regulated scanning Kelvin probe. Mild filiform corrosion was detected on all epoxy adhesive coated Zn-Al-Mg (ZM) surfaces during Cataplasma aging, suggesting anodic delamination as degradation mechanism. In contrast substantial cathodic delamination and blistering was observed for epoxy/electrogalvanized steel samples (ZE). Hence, HGM containing coatings can inverse effects on ZM or ZE coated steel, having important implications for industrial application. Highlights: Water-uptake in hollow glass microspheres. Corrosion resistance of hollow glass microspheres filled polymer coatings. Water absorption behavior of real adhesive systems. Cathodic and anodic delamination, scanning Kelvin probe. Comparison model formulation and commercial epoxy adhesive.